Shape and spin of minihaloes: from large scales to the centres - Druschke, Maik; Schauer, Anna T. P.; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The spin and shape of galaxies at the present day have been well studied both observationally and theoretically. At high redshifts, however, we have